Identity Representation in Customization. A Case of Nike Shoes - Kiet Tuan Nguyen; Phuong Van Nguyen; Khoa Anh Ngoc Le; Thao Danh Doan Bui (International Journal of Supply Chain Management, 2018)
Customization has been well-studied in perspective of manufacturers in the context of developed countries, however, not well-explored in developing countries like Vietnam. The present research was conducted to address customization as a value creator, associated withthe particularcase of Nike's shoes, for consumers in Vietnam. Based on prior studies, a model was built to examine customization through the meaning of customized products. This research aims to determineimportantfactors influencing the product meaning that young consumers use to evaluate Nike's products. Following a survey-based quantitative approach, Partial Least Square-Structural Equation Model (PLS-SEM) was used to analyze 227 participants, who have used Nike's products. The findings showed that personal identity-based motivation, social identity-based motivation, need for uniqueness, andaestheticimpressions wereimportantpredictors of customized Nike's shoes meaning, which influences consumer evaluation of the products.